Komunikasi Terapeutik Islam Sebagai Penanggulangan Problematika Psikologis Siswa-Siswi Madrasah - Moch Khafidz Fuad Raya (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2014)
Islam therapeutic communication is interpersonal communication that happen between the patients with a nurse to help the healing or recovery of the patient by providing suggestions interaction to help cure patients and to resolve the problems faced by patients, based on the principles of Islam. Patients who are referred madrasah students who have psychological problems faced as a result of the pressures in education, whether it is minimum target to be met, standardization, diverse array of student background, the complexity of the subject matter, to the problem lack of resources (both competencies, potential, and cost education) causes stress and problems on psychological. The research explores how Islam therapeutic communication can overcome the problems faced by psychology students madrasah. Therapeutic communication will be more meaningful if an educator interacts directly with students, especially by providing suggestions to strengthen the spiritual elements that will be positive suggestions for healing and psychological problems faced by students. In this case, the educators made himself a therapeutically through a variety of communication techniques optimally with the aim of changing the patient's behavior in a positive direction through the strengthening of Islamic values.